Desenvolvimento de biolubrificantes a base de óleo de moringa - Aquino, Carolina Barros (2018)
In recent years, pollution and environmental health aspects have become increasingly important as public issues. In this way, developing a product that conforms to the environment is of fundamental importance to minimize the evils caused by oil lubricants. In a world full of finite natural resources, mineral oils, from petroleum, bring consequences to the environment due to their low biodegradability and toxicity. Also consider, synthetic oils carry a high cost. The objective of this work is to analyze the tribological performance of the biolubrificant based on Moringa Oil. The biolubricant was extracted from moringa oil through the Soxhlet equipment and then added with iron oxide nanoparticles. The physicochemical analyzes were performed to characterize the biolubrificates based on pure moringa oil and the additive, such as density, acidity index, pH, humidity, infrared spectroscopy with Fourier transform and thermal analysis. For analysis of stability of the biolubrificante additive were performed zeta potential and particle size analysis. The tribological performance of the pure and additive lubricants was evaluated by the High Frequency Revirocating Rig (HFRR), which consists of a ball-plane wear test. The wear analysis was carried out using Scanning Electron Microscopy (SEM) analysis and the eschar diameter was analyzed from the wear with an optical microscope. The results showed that the moringa biolubrificant was successfully extracted and added as shown by its physicochemical characteristics. From the tribological point of view, it was verified that there was not a significant difference in the performance for the fluid added with iron oxide nanoparticles since this presented a higher coefficient of friction when compared to the pure oil.